Penerapan Arsitektur Pragmatis pada Rest Area KM 754 Sidoarjo - Anggraeni, Diva Istiana; Djuni, Erwin (JAUR (JOURNAL OF ARCHITECTURE AND URBANISM RESEARCH), 2025)
The KM 754 Sidoarjo Rest Area is a rest destination that combines practical aspects, efficiency and flexibility, into a comfortable and functional space for road users. With attention to user needs, this space not only offers essential amenities, but also provides an inviting atmosphere. Practical yet attractive architecture is a key feature, building a structure that is clearly recognized by drivers. An organized layout makes it easy to access facilities, while an organized parking area provides convenience for road users. Facilities such as restaurants, toilets and other services are strategically placed, ensuring efficient movement around the rest area. The main focus on efficiency can be seen from the careful arrangement of space, maximizing the use of each area without sacrificing comfort. The multi-use space concept exhibits flexibility, able to be adapted to various purposes, creating a dynamic environment according to individual preferences. Practicality, efficiency and flexibility are reflected in a wide choice of facilities tailored to visitor needs, creating a personalized rest experience. Thus, the KM 754 Sidoarjo Rest Area not only offers complete facilities, but is also a friendly, comfortable space and provides freedom of adaptation for road travelers. The concept of form and space considered in detail> emphasizes the superiority of this resting place, making it an unforgettable destination for travelers.